A building information modeling‐fire dynamics simulation integrated framework for the simulation of passive fire protection in a mid‐scale cross‐laminated timber compartment: Numerical implementation and benchmarking. (10th May 2022) - Sun, Qi; Turkan, Yelda; Fischer, Erica C.
Abstract: Construction fires are a big threat to worker safety and property safety. Mass timber buildings under construction are largely unprotected as they are not yet equipped with active fire protection systems. With the addition of Types IVA, B, and C, the 2021 International Building Code adopted stricter requirements for mass timber buildings that are under construction. Cross‐laminated timber (CLT) is used as the primary structural element for high‐rise mass timber buildings. However, to date, limited number of research studies investigated the impact of passive fire protection for CLT buildings that are under construction. To facilitate a better understanding of construction fires and their consequences, it is necessary to develop a numerical modeling solution for the early phases of a CLT construction project, which can be achieved by using building information models together with fire dynamics simulation (FDS). However, the numerical modeling technique must be benchmarked against experimental data first to then extrapolate the modeling technique to explore other parameters and conduct FDS analysis. Therefore, this paper develops and benchmarks a numerical modeling solution against a mid‐scale CLT compartment fire test by applying the FDS tool to simulate the fire behavior within the CLT compartment. The FDS analysis results are expected to validate the practicality of simulating the fire behavior in CLT structures using the numerical model proposed in this study. The overarching goal of this study is therefore to develop a comprehensive numerical modeling solution to simulate and assess passive fire protection sequencing in CLT buildings that are under construction.